2023
DOI: 10.3390/ijerph20053933
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Nurse Satisfaction with Supervisor Leadership

Abstract: The satisfaction of nurses with the leadership of their supervisors exerts a positive association with their job satisfaction. This study identified factors associated with nurse satisfaction with supervisor leadership and developed a model of causal relationships based on social exchange theory. A satisfaction scale was developed to measure how nurses felt about the leadership of their supervisor, which also assessed the validity and reliability using a cross-sectional descriptive survey questionnaire adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The goal of instituting clinical supervision is to strengthen the continuous nursing process and to guarantee that every member of the nursing staff does their duties to the best of their abilities in accordance with the rules or orders. All nursing staff members participate in supervision activities as both subjects and objects [50]. In the field of nursing, supervision is employed to guarantee that actions are carried out in accordance with established standards and the vision, purpose, and goals of the organization.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of instituting clinical supervision is to strengthen the continuous nursing process and to guarantee that every member of the nursing staff does their duties to the best of their abilities in accordance with the rules or orders. All nursing staff members participate in supervision activities as both subjects and objects [50]. In the field of nursing, supervision is employed to guarantee that actions are carried out in accordance with established standards and the vision, purpose, and goals of the organization.…”
Section: Discussionmentioning
confidence: 99%
“…Many types of incentives could work for nurses, including financial incentives, flexible work schedules, education, overtime pay, tuition reimbursement, and recognition [35]. Incentives are appreciated by nurses and enhance their satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…These procedures can increase workers' commitment to their work and levels of job satisfaction. These procedures consist of reworking jobs, providing performance reviews, investing in training and development, and including staff members in decision-making [2]. In contrast, one of the most important factors in determining employee satisfaction is supervisory support.…”
Section: High Performance Work System (Hpws)mentioning
confidence: 99%
“…An engaged workplace can boost employee trust and job happiness. Supervisors that exhibit open communication, respect, and concern for their staff members can foster this atmosphere [2]. In addition, studies have demonstrated that positive management practices like vocal encouragement, constructive criticism, and problem-solving assistance greatly increase worker job satisfaction [15].…”
Section: High Performance Work System (Hpws)mentioning
confidence: 99%
See 1 more Smart Citation